Gestión del talento humano en el comercial Mega-Propinec. - Gonzales Carpio, Jenniffer Del Roció (2022)
The main objective of the present case is of great interest because it focuses on the analysis of the management of human talent, the study of the "Mega proprinec commercial" of the city of Babahoyo, which allows to publicize the facts for which no presents an appropriate physical space to be able to promote its multiplicity of products offered by this marketer, this is due to the buildings that exist around it since, due to these buildings, the Mega proprinec commissary cannot offer a large and comfortable place for attention of its clients, with the current work it will be determined to identify the effects that have affected the commercial. In Chapter I the part of reference to the research objectives will be made. In Chapter II, the development of the framework is carried out, where the background of the research, theoretical framework, assumptions and variables are presented. In Chapter III the results of the investigation are developed. In chapter IV and V, respectively, the conclusions and recommendations are made. Chapter VI is where the intervention proposal of this research is developed. And in Chapters VII and VIII are the bibliography and research x.